Functional and radiological outcome in distal radius fractures treated with locking compression plate - Chavhan, Ashish N.; Dudhekar, Ulhas J.; Badole, Chandrashekhar M.; Wandile, Kiran N. (International Journal of Research in Medical Sciences, 2017)
Background: Fractures of distal end of radius are one of the most common skeletal injuries encountered in orthopaedics. There are various modalities for treatment like close reduction and cast application, external fixators, ORIF with plate etc. CR and cast application or K-wire fixation, external fixation is associated with immobilisation, wrist stiffness, loss of reduction postoperatively. So we performed volar plating for distal end radius fractures and calculated its results. Methods: We performed ORIF with plating (Volar approach) in 35 patients (22 male and 13 female) of distal end radius fractures depending on inclusion and exclusion criteria. Fractures were classified according to AO classification. All patients were operated under tourniquet. Results were analysed using Mayo score. Results: Out of 35 patients, 14 had type A, 16 had type B and 5 had type C fractures (AO classification). Average operative time was 45 minutes and blood loss of 50 ml. Average time to clinico-radiological union was 7 weeks. Average follow up time was 8 months. Average time to wrist mobilisation was 8 days. According to Mayo score, 16 patients had excellent results, 15 had well and 4 had satisfactory results. Conclusions: Volar plating for fracture distal end radius reduces chances of wrist joint stiffness and loss of reduction and good results can be obtained. So in our opinion, volar plating for treatment of fracture distal end radius is good method with excellent outcomes.